Enhancing SMEs’ data analytics capability through university tie-ups - PAN, Gary (Institutional Knowledge at Singapore Management University, 2019)
Harnessing the power of data analytics, SMEs can now generate visualisations of the company's historical data to date, and predictions for the future - something which is nearly impossible before the era of big data.